Men and Women's Education and Illiteracy in Adrar Speech Community - Bachir Bouhania, Algeria- الجزائر (College of Education for Women, 2019)
In Algeria, education is compulsory for males and females. This foundational decision was taken right after the independence of the country in 1962. Soon after, in 1963, the central government decided the Arabisation of the whole educational levels starting from primary school till university. At the same period, illiteracy-eradication programmes were launched by the Ministry of Education to get rid of this post-colonial scourge. In the administrative department (or Wilaya) of Adrar, former Tuat, young males and females attend Quranic schools (Zawaya) well before any formal education, that is as early as 4-5 years of age. The adult people who are not enrolled in formal classes could sit for non-formal ones. However, actual measurements and statistics reveal that the number of male and female pupils is not balanced: The present research paper aims at describing this phenomenon through statistics provided by the last National Census (2008), Adrar local educational academy, and Adrar Illiteracy-eradication Centre. The methodology consists in interviewing representatives and directors of the aforementioned institutions and surveying their archives and enrollment registers. The overall results show that the boys are more numerous than the girls in formal schools, while the reverse trend is noticed in Illiteracy-eradication classes where women are more present than men. From sociological and sociolinguistic viewpoints, women's increase of attendance of illiteracy-eradication classes can be interpreted as their attempt at having a certain educational level to overcome societal difficulties, at climbing up the social ladder, and at securing prestigious social positions within the community.